(untitled) (Costos y Gestión, 2023)
This paper applies a marginal approach to the performance indicator Operating Leverage (LO) and explores different ways to achieving the goal of a value equal to zero, meaning to reach an identical percentage variation of revenues and costs. It seeks to gain a deep understanding of what alternatives are available to achieve this goal, in the context of a strategy-integrated budgeting process. We will begin by analyzing the simple production case, where we will find the values of each variable of the outcome equation (Q, FC, vc and p) that, ceteris paribus, would verify a value of zero in the LO. Next, we will graphically compare the physical quantity of sales that determines a LO equal to zero with the break-even point, and we will make some considerations regarding changes in the amount of fixed costs. Subsequently, we will propose an orderly methodological framework to achieve the goal of LO equal to zero by combining changes in the variables according to our capability to influence them. Then, we will extend the analysis to the case of multi-production, where we will start assuming the maintenance of the sales structure between the analyzed period and the prior, to finally lift this assumption.